KONSEP DAN NILAI-NILAI MULTIKULTURALISME DALAM PENDIDIKAN DASAR ISLAM - Zulkarnaen, Muhammad (UIN Antasari Banjarmasin, 2020)
ABSTRACTThis paper discusses the concepts and values of multiculturalism in Islamic basic education and how it is relevant to Islamic basic education itself. Multiculturalism is a relatively new concept in the scientific treasures, especially in the social sciences, so the concept of multiculturalism is very important to be introduced and included in the realm of education, especially Islamic basic education as multicultural values should be taught from an early age to raise awareness of the importance of justice and equality. The multicultural concept has noble values such as justice, tolerance, human rights, justice and gender equality.KEYWORDS: Multiculturalism Values; Islamic Basic Education; Knowledge Treasure. ABSTRAKTulisan ini membahas tentang konsep dan nilai-nilai multikulturalime dalam pendidikan dasar Islam dan bagaimana relevansinya terhadap pendidikan dasar Islam itu sendiri. Multikulturalisme merupakan suatu konsep yang relatif paling anyar dalam khazanah ilmu pengetahuan, khususnya dalam ilmu-ilmu sosial, sehingga konsep multikultural sangat penting untuk dikenalkan dan masuk dalam ranah pendidikan, terutama pendidikan dasar Islam sebagaimana nilai-nilai multikultural sebaiknya diajarkan sedari dini untuk menumbuhkan kesadaran pentingnya perbedaan dan kesetaraan keadilan. Konsep multikultural memiliki nilai-nilai yang luhur seperti keadilan, toleransi, HAM, keadilan dan kesetaraan gender.KATA KUNCI: Nilai-Nilai Multikulturalisme; Pendidikan Dasar Islam; Khazanah Ilmu.